Microcirculatory disorders in scleroderma systematica: an association with vascular wall stiffness - Ulyana Yuryevna Ruzhentsova (Научно-практическая ревматология)
Objective: to study the specific features of regulation of peripheral vascular tone and their association with the endothelial structure and function of large vessels in patients with scleroderma systematica (SDS). Subjects and methods. The investigation enrolled 25 patients with SDS (mean age, 47±2.6 years; mean disease duration, 8.3+1.7 years) and 15 apparently healthy individuals matched for age and gender. Comprehensive examination involved laboratory and instrumental studies, laser Doppler study to evaluate endothelium-dependent and endothelium-independent vasodilation, as well as applanation tonometry calculating the pulse wave velocity and augmentation index. Results. All the patients were found to have impaired peripheral vascular responsiveness as compared to the controls. The examination established a relationship between the magnitude of endothelium-dependent vasodilation and the stiffness index of large vessels. There was no association between endothelium-independent vasodilation and vascular elasticity parameters.